Sustained Release of VEGF to Promote Angiogenesis and Osteointegration of Three-Dimensional Printed Biomimetic Titanium Alloy Implants - Li, Youbin; Liu, Yuzhe; Bai, Haotian; Li, Ronghang; Shang, Jing; Zhu, Zhengqing; Zhu, Liwei; Zhu, Chenyi; Che, Zhenjia; Wang, Jincheng; Liu, He; Huang, Lanfeng (Frontiers in Bioengineering and Biotechnology, 2021)
Tumor resection and treatment of trauma-related regional large bone defects have major challenges in the field of orthopedics. Scaffolds that treat bone defects are the focus of bone tissue engineering. 3D printing porous titanium alloy scaffolds, prepared via electron beam melting (EBM) technology, possess customized structure and strength. The addition of a growth factor coating to the scaffold introduces a specific form of biological activation. Vascular endothelial growth factor (VEGF) is key to angiogenesis and osteogenesis in vivo. We designed a porous titanium alloy scaffold/thermosensitive collagen hydrogel system, equipped with VEGF, to promote local osseointegration and angiogenesis. We also verified the VEGF release via thermosensitive collagen and proliferation and induction of the human umbilical vein endothelial cells (HUVECs) via the composite system in vitro. In vivo, using micro-CT, histology, and immunohistochemistry analysis, we confirmed that the composite scaffold aids in angiogenesis-mediated bone regeneration, and promotes significantly more bone integration. We also discovered that the composite scaffold has excellent biocompatibility, provides bioactive VEGF for angiogenesis and osteointegration, and provides an important theoretical basis for the restoration of local blood supply and strengthening of bone integration.